HADITHS RELATED TO THE ETHICS OF HONEST AND RESPONSIBLE COMMUNICATION - Lubis, Muya Syaroh Iwanda; Nurhayati, Nurhayati (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2023)
ABSTRACTÂ The Prophet (peace and blessings of Allah be upon him) said: â€œThe dirty word shows the dirty habits and the dusty habits in hell.â€ (HR Al-Bukhari and At-Tirmidzi) In todayâ€™s advanced internet world, interpersonal communication is as far away as possible. People in one country can communicate with other people in different countries at the same time. Especially with social media. In short, the problem of interpersonal communication in this century is relatively no obstacle, it is considered something less if no communication funds talk about things that are not important and have interest.Â  And the problem is the content or material of that communication which then becomes a discussion among the wider community. Islamic communications include all the teachings of Islam, including Akidah (belief), Shariah (Islam), and Akhlak. (ihsan).In the Qurâ€™an and Hadith there are guidelines for good and effective communication. We can describe it as a rule, principle, or ethics of communicating in the perspective of Islam. Â Keywords: Hadiths, honest, responsible communication